PENGARUH PENGALAMAN AUDITOR, INDEPENDENSI, SKEPTISME PROFESIONAL DAN TIPE KEPRIBADIAN TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (Studi Empiris Pada KAP Di Wilayah Pekanbaru, Padang dan Batam) - Arbaiti, Arbaiti; Alfiati Silf, Alfiati Silf; L, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The research aims to determine the effect of experience auditor, Independency, Professional Skepticism, types of personality to fraud detection ability of auditor (empirical studies on publik accounting firm in Pekanbaru, Padang, and Batam). The methods used in this research was multiple linear regression. Testing the validity and reliability questionnaire in this study using SPSS (Statistical Product and Service Soluction). The sampling methods used was convenience sampling which counted 20 in 2018. Respondents used in this study were partners, managers,supervisors, senior and junior auditors. Data collected by distributing questionnairs to 105 auditor working in 20 public accounting firm, but only 70 questionnaires were returned and can be processed. The results of the hypothesis test showed that experience auditor, independency, professional skepticism and types of personality has an effect on fraud detection ability of auditor with 0,004, 0,002, 0,046 and 0,012 significance.Keywords : Experience Auditor, Independency, Professional Skepticism, types of personality and Fraud Detection Ability Of Auditor.